2018
DOI: 10.3389/fimmu.2018.01823
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Exploit Notch Signaling to Redefine a Supportive Cytokine Milieu

Abstract: Notch signaling is a well-known key player in the communication between adjacent cells during organ development, when it controls several processes involved in cell differentiation. Notch-mediated communication may occur through the interaction of Notch receptors with ligands on adjacent cells or by a paracrine/endocrine fashion, through soluble molecules that can mediate the communication between cells at distant sites. Dysregulation of Notch pathway causes a number of disorders, including cancer. Notch hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 287 publications
(360 reference statements)
1
43
0
Order By: Relevance
“…Tumor cells can excrete many types of cytokines, such as VEGFA and TNF-α, thereby altering the permeability of microvascular networks and causing transudative and exudative ascites 43 , 44 . Macrophage and inflammatory cells could induce pyroptosis or necroptosis, release several necrotic materials and inflammatory mediators, and increase the volume of ascites 8 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells can excrete many types of cytokines, such as VEGFA and TNF-α, thereby altering the permeability of microvascular networks and causing transudative and exudative ascites 43 , 44 . Macrophage and inflammatory cells could induce pyroptosis or necroptosis, release several necrotic materials and inflammatory mediators, and increase the volume of ascites 8 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…25 In this study, we first analysed the GSE10 8989 data set to investigate the effects of Notch signalling pathway mutations on the immunophenotype of CRC, which differs from the aim It has been reported that the dysregulation of the Notch pathway in the tumour skews the local cytokine milieu, shaping the immunological landscape and affecting tumour growth, progression and metastases. 26 The Notch signalling pathway is a key regulator of inflammatory-related cytokines in cancers, such as IL-10, 27 TGFβ, 28 IL-6, 29 CCL2 30 and CXCL12. 31 In our study, we observed that the expression of CXCR3 was up-regulated in cluster 4 (mainly from tumours of patients with Notch pathway mutations) compared with cluster 0 (mainly from tumours of non-mutation patients) of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is an evolutionarily rmly conserved signaling system.It widely exists in all known animal cells and regulates the proliferation, differentiation and apoptosis of tissues and cells.VEGF-notch signal cause tumor abnormal vascular growth through controlling tip and stalk cells balance [18,19].…”
Section: Vegf-notch Connection Detectionmentioning
confidence: 99%